Ball Direction Prediction for Wheeled Soccer Robot Goalkeeper Using Trigonometry Technique - Bagus Setiawan, Danis; Khumaidi, Agus; Priyonggo, Projek; Basuki Rahmat, Mohammad; Sutrisno, Imam; Nasikhin, Khoirun; Wisnu Sahputera, Adi (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2019)
In this research Trigonometry Technique was implemented to predict the ball movement direction for Wheeled Soccer Robot Goalkeeper. The performance of goalkeeper robot in Wheeled Soccer Robot Contest is very important. The crucial problem with goalkeeper robot is the delay in ball detection by the camera because the results of the camera images captured are always slower than the pictures that have been captured. This causes the robot's response to blocking the opponent's kick ball being late. Trigonometry Technique is one technique that can be used to predict the direction of the ball movement based on trigonometry mathematical formulas. The input data used is the location of the last ball position (x?last ball and y-last ball) and the location of the current ball position (x-current ball and y-current ball). The outputs are the prediction of the next ball location (x-predict ball and y-predict ball) and the prediction of ball movement direction prediction. The results are the goalkeeper's robot successfully predicts the opponent's kick direction with 90% accuracy and can predict the location of the next ball very well. By implementing this method, it is expected to optimize the performance of the goalkeeper robot in saving the goal.